EXPERIENCE OF APPLICATION OF SAZAR IN POLYTHERAPY AT SICK OF THE EPILEPSY WITH PARTIAL AND GENERALIZED TONIC-CLONIC CONVULSIVE ATTACKS - A. S. Shershever; E. V. Sorokova; A. Y. Lazarev (Эпилепсия и пароксизмальные состояния)
Studied efficiency of application Sazar (lamotrigin, Alcaloid, Macedonia) in polytherapy at sick of an epilepsy with partial and generalized tonic-clonic convulsive attacks, and also dynamics of disturbing frustration with application of a scale of alarm of Hamilton (HARS) and activity of vegetative nervous system on an index of Kerdo. 214 patients at the age from 15 to 71 years are treated. Used doses of a preparation from 150 mg to 450 mg per day. Research has shown that preparation action comparably on anti-spasm to effect with action lamotrigin. In groups of patients with cryptogenic and a symptomatic epilepsy reduction of quantity of attacks more than on 50% through 12 months after Sazar addition, and in group with an idiopathic epilepsy reduction of attacks more than on 90% per month were noted. The influence spectrum on symptoms of alarm and an index of Kerdo has appeared uniform throughout all period of supervision from 8 to 22 months.